Loneliness among elderly in community residence at Pontian district, Johore - Rohani Mamat; Hussein S Z; Shamsudin K (Malaysian Journal of Medicine and Health Sciences, 2020)
Loneliness is a major social problem among the elderly that has gone through almost all countries in the world. Even though loneliness is seen as the health-threatening but, the loneliness assessment is still marginal¬ized in routine medical check-up for every senior citizen. Methods: This is a sequential explanatory mixed-method study with a cross-sectional community survey was conducted among 380 community residence elderly followed by in-depth interview among eight respondents. This study aims to measure the loneliness and to explore loneliness experienced by older adults. Data were collected using the short form of Social and Emotional Loneliness Scale for Adults (SELSA-S) and data were analysed using SPSS (version 23.0) for windows. In the qualitative study, eight re¬spondents were interviewed face-to-face and data were analysed using thematic analysis Braun and Clarke (2006). Results: The results revealed that 37.2% of respondents had loneliness. Bivariate analyses showed the age, level of education and marital status were significantly associated with loneliness. The results of multiple logistic regression discovered gender (OR=1.75,95%CI:1.04-2.93; p=0.03) and marital status (OR=2.24,95%CI: 1.33-3.77;p= 0.002) were a significant predictor of loneliness. In a qualitative study, the result showed two main themes were recorded as causes of loneliness among the elderly are ‘changing the lifestyles’ and ‘ineffective communications. The sub-themes included ‘loss of someone who significant’, ‘limited physical mobility’, ‘all alone’ and ‘no support’. Conclusion: The issue of loneliness needs critically to be addressed even though Malaysia has not reached the ‘aging population’, but the loneliness prevalence experienced by the older adult has similarities with other countries that have attained that status.